The Impact of Unpredictability on Dyspnea Perception, Anxiety and Interoceptive Error Processing - Tan, Yafei; Van den Bergh, Omer; Qiu, Jiang; von Leupoldt, Andreas (Frontiers in Physiology, 2019)
Dyspnea is a prevalent interoceptive sensation and the aversive cardinal symptom in many cardiorespiratory diseases as well as in mental disorders. Especially the unpredictability of the occurrence of dyspnea episodes has been suggested to be highly anxiety provoking for affected patients. Moreover, previous studies demonstrated that unpredictable exteroceptive stimuli increased self-reports and electrophysiological responses of anxiety such as the startle probe N100 as well as amplified the processing of errors as reflected by greater error-related negativity (ERN). However, studies directly examining the role of unpredictability on dyspnea perception, anxiety and error processing are widely absent. Using high-density electroencephalography, the present study investigated whether unpredictable compared to predictable dyspnea would increase the perception of dyspnea, anxiety and interoceptive error processing. Thirty-two healthy participants performed a respiratory forced choice reaction time task to elicit an interoceptive ERN during two conditions: an unpredictable and a predictable resistive load-induced dyspnea condition. Predictability was manipulated by pairing (predictable condition) or not pairing (unpredictable condition) dyspnea with a startle tone probe. Self-reports of dyspnea and affective state as well as the startle probe N100 and interoceptive ERN were measured. The results demonstrated greater dyspnea unpleasantness in the unpredictable compared to the predictable condition. Post-hoc analyses revealed that this was paralleled by greater anxiety, and greater amplitudes for the startle probe N100 and the interoceptive ERN during the unpredictable relative to the predictable condition, but only when the unpredictable condition was experienced in the first experimental block. Furthermore, higher trait-like anxiety sensitivity was associated with higher ratings for dyspnea unpleasantness and experimental state anxiety ratings. The present findings suggest that unpredictability increases the perception of dyspnea unpleasantness. This effect seems related to increased state and trait anxiety and interoceptive error processing, especially when upcoming dyspnea is particularly unpredictable, such as in early experimental phases. Future studies are required to further substantiate these findings in patients suffering from dyspnea.